2011
DOI: 10.1369/0022155411408315
|View full text |Cite
|
Sign up to set email alerts
|

The Open Microcirculation in Human Spleens

Abstract: It has long been debated whether the red pulp of human spleens harbors an open or a closed microcirculation or both. To solve this issue, the authors differentially stained the endothelium in red pulp arterial microvessels and in venous sinuses using brightfield and fluorescence immunohistology with reagents against CD34 and CD141. Three-dimensional models of red pulp arterial microvessels and sinuses were derived from serial double-stained paraffin sections with the help of license-free open-access software. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…However, a 3D reconstruction of the serial sections is a powerful tool that can be used to investigate the splenic microvasculature, because it can provide a 3D conception of the vessels and their surrounding structures. Indeed, this technique was previously applied to an analysis of the branching pattern of the central artery, as well as to a demonstration of the open microcirculation in the human spleen (11,16). In the present study, we performed 3D reconstructions of the vasculature and the white pulp in the human spleen using CD34 immunostained sections.…”
Section: Arterial Vasculature In Human Splenic Folliclesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a 3D reconstruction of the serial sections is a powerful tool that can be used to investigate the splenic microvasculature, because it can provide a 3D conception of the vessels and their surrounding structures. Indeed, this technique was previously applied to an analysis of the branching pattern of the central artery, as well as to a demonstration of the open microcirculation in the human spleen (11,16). In the present study, we performed 3D reconstructions of the vasculature and the white pulp in the human spleen using CD34 immunostained sections.…”
Section: Arterial Vasculature In Human Splenic Folliclesmentioning
confidence: 99%
“…SEM of vascular corrosion casts of the human spleen (7) has further confirmed that some of the penicillar arteries, after passing through a splenic follicle, make a hairpin turn and return to the follicle to form bundler arteries. Immunohistochemical studies have focused on the vasculature of the human spleen (11)(12)(13)(14)(15)(16)(17)(18)(19). Steiniger et al performed double staining of serial sections of human spleens for CD34 (a marker for the vascular endothelium) and CD141 (a marker for the sinus en-oxidase activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional interpretation of the phenomenon is that splenectomy removes the decisive recirculation compartment, which maintains MZ B‐cell vitality and function. MZ B‐cell survival may depend on bacterial or viral components that are directly extracted from the blood, because the human spleen most likely has an entirely open microcirculation . This means, that capillaries of the human splenic red pulp do not join the venous sinuses, but pour their blood into the loose connective tissue of the splenic cords through open ends.…”
Section: Introductionmentioning
confidence: 99%
“…The blood elements with undisturbed elasticity of cell membrane subsequently return to the blood circulation by penetrating through the small openings in the walls of specialized capillaries (splenic venous sinuses) (ref. [7][8][9][10] ). The altered erythrocytes in hereditary spherocytosis are vulnerable to splenic sequestration and subsequent lysis and cause the characteristics of this disease such as jaundice, anemia, splenomegaly, and cholelithiasis.…”
Section: Introductionmentioning
confidence: 99%